2018
DOI: 10.1186/s12906-018-2150-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of complementary and alternative medicine by patients with cancer: a cross-sectional survey in Saudi Arabia

Abstract: BackgroundA significant proportion of cancer patients use complementary and alternative medicine (CAM) along with conventional therapies (CT), whereas a smaller proportion delay or defer CT in favor of CAM. Previous studies exploring CAM use among cancer patients in the Middle East region have shown discrepant results. This study investigates the prevalence and pattern of CAM use by Saudi cancer patients. It also discusses the possible benefits and harm related to CAM use by cancer patients, and it explores th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
90
4
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 27 publications
11
90
4
3
Order By: Relevance
“…4,14 This correlation with religion and spiritual practices of CAM was already suggested in previous studies. 8,16 Also consistent with the literature, our study identified the main reason for CAM use was to improve overall health, and less often to treat specific symptoms or problems. 8,17 Treatment for specific problem/health issues, such as bladder symptoms, fatigue, balance issues, tremors, spasticity, stress and MS relapses were also less commonly mentioned reasons to use CAM.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…4,14 This correlation with religion and spiritual practices of CAM was already suggested in previous studies. 8,16 Also consistent with the literature, our study identified the main reason for CAM use was to improve overall health, and less often to treat specific symptoms or problems. 8,17 Treatment for specific problem/health issues, such as bladder symptoms, fatigue, balance issues, tremors, spasticity, stress and MS relapses were also less commonly mentioned reasons to use CAM.…”
supporting
confidence: 86%
“…8,16 Also consistent with the literature, our study identified the main reason for CAM use was to improve overall health, and less often to treat specific symptoms or problems. 8,17 Treatment for specific problem/health issues, such as bladder symptoms, fatigue, balance issues, tremors, spasticity, stress and MS relapses were also less commonly mentioned reasons to use CAM. Nineteen percent of the patients were using CAM to address multiple issues, as shown in Figure 1.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Camel urine is believed to have therapeutic effects in the treatment of cancer, diabetes, certain infectious and cardiovascular diseases as well as in the treatment of hair and skin problems. Hence, fresh urine is consumed, used to wash body and hair, and is a component in ointments (Alkhamees, 2017;Gader, 2016) for example it has been described that Bedouins in the Middle East have a daily consumption of 100 ml camel urine while a study amongst 156 Saudi cancer patients showed that 15.7% drank camel urine (Abuelgasim, 2018;Al-Yousef et al, 2012).…”
Section: Failure To Detect Mers-cov Rna In Urine Of Naturally Infectementioning
confidence: 99%